Doris Miller, Pearl Harbor, and the Birth of the Civil Rights Movement - Cutrer, Thomas W.; Parrish, T. Michael (Book collections on Project MUSE., 2018)
This is the story of Ship's Cook Third Class Doris "Dorie" Miller who, on the morning of December 7, 1941, after serving breakfast and turning his attention to laundry services aboard the USS West Virginia, heard the alarm calling sailors to battle stations. The first of several torpedoes dropped from Japanese aircraft had struck the American battleship. Miller hastily made his way to a central point and was soon called to the bridge by Lt. Com. Doir C. Johnson to assist the mortally wounded ship's captain, Mervyn Bennion. Miller then joined two others in loading and firing an unmanned anti-aircraft machine gun--a weapon that, as an African American in a segregated military, Miller had not been trained to operate. But he did, firing the weapon on attacking Japanese aircraft until the .50-caliber gun ran out of ammunition. For these actions, Miller was later awarded the Navy Cross, the third-highest naval award for combat gallantry.